2019
DOI: 10.1016/j.spinee.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Trends in lumbar radiofrequency ablation utilization from 2007 to 2016

Abstract: Background Context: Lumbar radiofrequency ablation (RFA) is an intervention used to treat facet-mediated chronic low back pain. In some studies with methods consistent with clinical practice guidelines, RFA results in improvements in pain and functional limitations. However, in other studies, RFA demonstrates limited benefit. Despite unanswered questions regarding efficacy of RFA, its use is widespread. Purpose: To describe trends in the utilization and cost of lumbar RFA and lumbar facet injections. Study Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 35 publications
0
17
1
Order By: Relevance
“…This diagnosis is prevalent in approximately 45% of lower back pain patients. [35][36][37][38] While LRFN is one of the best studied interventional pain procedures, it is also one of the most debated procedures with constantly evolving evidence. 39,40…”
Section: Lumbar Medial Branch Radiofrequency Neurotomymentioning
confidence: 99%
“…This diagnosis is prevalent in approximately 45% of lower back pain patients. [35][36][37][38] While LRFN is one of the best studied interventional pain procedures, it is also one of the most debated procedures with constantly evolving evidence. 39,40…”
Section: Lumbar Medial Branch Radiofrequency Neurotomymentioning
confidence: 99%
“… 12 For lumbar RFA, a recent review of the Marketscan commercial claims and encounters databases from 2007 to 2016 demonstrated a 130.6% overall increase in utilization (9.7% annually). 13 Along with increasing utilization, there was also a reciprocal increase in cost, with the cost per 100 000 enrollees increasing from US$94 570 in 2007 to US$266 680 in 2016 (12.2% annual increase). In addition, the high number of blocks is inconsistent with the most commonly cited prevalence rates, which are generally <15% in the non-elderly, but increase with age.…”
Section: Introductionmentioning
confidence: 99%
“…12 For lumbar RFA, a recent review of the Marketscan commercial claims and encounters databases from 2007 to 2016 demonstrated a 130.6% overall increase in utilization (9.7% annually). 13 Along with increasing utilization, there was also a reciprocal increase in cost, Table 2 What the grades of evidence mean and suggestions for practice…”
Section: Introductionmentioning
confidence: 99%
“…The utilization patterns of facet joint interventions have been well studied with overall increases until 2009 and a trend of decline since 2009 (30)(31)(32)(33)(34)(35)(36)(37). These studies also showed the reversal of the ratio of lumbosacral facet joint injections compared with facet joint neurolytic procedures, decreasing from 6.7% in 2009 to 2.2% in 2016.…”
mentioning
confidence: 99%